RANCANG BANGUN APLIKASI PENCATATAN PERKIMTAN DENGAN METODE WATERFALL DI KOTA BATAM - brantaricke; Pastima Simanjuntak (Computer Science and Industrial Engineering, 2024)
The Public Housing, Settlements and Parks Service (Disperkim) is an agency within the Batam City Public Housing, Settlements and Parks Service. As a document recorder of incoming and outgoing letters, Disperkim is expected to be able to provide administrative services related to conveying information, recording payment data to occupant data and low-cost housing data itself. Currently Disperkim still uses manual methods to manage data, namely with Microsoft Excel. This has an impact on the process of incoming and outgoing mail. Reporting data to leaders who still use manuals is often a problem in correspondence. So we need a system that can help admins in recording letters. This system was built using the PHP programming language and uses the waterfall method and MySql as the database. The aim of this research is to assist management in managing data in the Batam City Public Housing, Settlement and Parks Department and provide easy access to web-based incoming and outgoing letters. The advantage of this system is that it can be accessed anywhere as long as it is connected to the internet, and the existence of a database makes this system better in terms of cost compared to the system implemented previously.